IMMANENCE AND THE PRINCIPLE OF ULTIMACY IN THE DIMASA CULTURE OF NORTHEAST INDIA - Hasnu, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Dimasa, a tribal community in Northeast India, enjoy a long and proud heritage. Their creation stories, their celebrations of sacrifices and particularly the thanksgiving festival Bushu/Busu (harvesting festival), and their beliefs about death and afterlife are examined. Their stories, practices, and culture reveal a society that presents a non-dualistic, immanent worldview.